Aortic dilatation and outcome in women with Turner syndrome. Issue 9 (27th October 2018) - Duijnhouwer, Anthonie L; Bons, Lidia R; Timmers, Henri J L M; van Kimmenade, Roland R L; Snoeren, Miranda; Timmermans, Janneke; van den Hoven, Allard T; Kempers, Marlies; van Dijk, Arie P J; Fleischer, Kathrin; Roos-Hesselink, Jolien W
Abstract : Background: Women with Turner syndrome (TS) are at increased risk of aortic dissection, which is related to ascending aortic diameter. However, the relation between aortic diameter and outcome is not well determined. This study evaluates the prevalence of aortic dilatation, the growth rate of the aorta and the risk of aortic complications in adults with TS. Methods: Single centre, retrospective study of all women with TS followed with a strict protocol in an outpatient TS clinic. Aortic diameters were analysed using advanced imaging. The primary outcome was a combined endpoint of aortic-related mortality, aortic dissection and preventive aortic surgery. The secondary endpoint was aortic growth and prevalence of aortic dilatation, defined as an aortic size index >20 mm/m 2 at baseline. Results: At least one cardiac MR/CT was available in 268 women with TS, having median age of 28.7 (IQR: 21.3–39.7) years. Aortic dilatation was present in 22%. Linear regression identified independent factors associated with larger aortic diameters: age (coefficient=0.23; p<0.001), hypertension (coefficient=2.7; p<0.001), bicuspid aortic valve (coefficient=3.3; p<0.001), 45XO karyotype (coefficient=1.7; p=0.002), weight (coefficient=0.075; p<0.001) and growth hormone treatment (coefficient=1.4; p=0.044). During follow-up (6.8±3.2 years), five women (2%) reached the primary endpoint (two dissections, three aortic surgery). Women withmore than one scan (n=171; 1015 patient-years follow-up), the median aortic growth was 0.20 (IQR: 0.00–0.44) mm/year. In multivariate analysis, aortic growth was not associated with baseline aortic diameter or other variables. Conclusions: Aortic dilatation is common and known associations were confirmed in large adult TS cohort However, aortic dissection, related mortality and preventive aortic surgery are rare. Growth hormone treatment in childhood was associated with aortic dimensions.